Practice of non-pharmacological post-operative pain management and associated factors among nurses working in public referral hospitals of Amhara regional state, Ethiopia, 2019 - Dejen Getaneh Feleke; Ermias Sisay Chanie; Sheganew Fetene Tassaw; Tadila Dires (Elsevier, 2024)
Background: Postoperative pain is a combined effect of several unpleasant sensory, emotional and mental experiences. Patient's previous experiences, nature and duration of surgery, site and size of the incision and the extent of surgical trauma are some of the factors affecting the degree of post-operative pain. Objectives: To assess practice of non-pharmacological post-operative pain management and associated factors among nurses working in public referral hospitals of Amhara regional state, Ethiopia. Method: Institutional based cross-sectional study was conducted among nurses working in public referral hospitals of Amhara regional state, Ethiopia from March to April 2019. Census method was employed to select study participants. Data were entered into Epi info version 7.2.0.1 and exported to SPSS window version 20 for analysis. Binary and multivariable logistic regression was used to see the association between dependent and independent variables. The odds ratio with a 95 % confidence interval was computed. P-value < 0.05 was used to declare association. Results: Three hundred nurses working in post-operative units of selected referral hospitals of Amhara regional state were involved in the study. The respondents' ages (Mean ± SD.) were (29.8 ± 7.3) years and their experience (Mean ± SD) post-operative unit was (3.8 ± 3.3) years. Majority (59.7 %) of the respondents were females. This study revealed that about 50.2 % of nurses were not applied non-pharmacological post-operative pain management techniques for their patients. Nurse's educational status, attendance of training, attitude of nurses, willingness of patients, experience in nursing, marital status and working unit were associated with practice of non-pharmacological post-operative pain management with p-value of < 0.05. Conclusion: In this study, nearly half of nurses didn't apply non-pharmacologic pain management techniques for patients when they had pain. In-service training and educational development are recommended for nurses about non-pharmacologic pain management.